COMPARATIVE EFFICACY OF METHYLPREDNISOLONE AND DEXAMETHASONE IN INTENSIVE CARE PATIENTS WITH SEVERE COVID-19: A PROSPECTIVE STUDY FROM PAKISTAN - HASHMI , MS; NAEEM , H; HUSSAIN, A; ZAFAR, GM; RAO, MA; JEHANGIR , HMS; KHOKHAR, HS; ZAHOOR, S (Biological and Clinical Sciences Research Journal, 2022)
The study aimed to determine the comparative efficacy of dexamethasone and methylprednisolone in treating severely ill COVID-19 patients in terms of mortality. Using a quasi-experimental design, the study was conducted at Mayo Hospital, Lahore, from May 2021 to October 2021. A total of 148 patients, divided into two groups of 74 each (groups A and B), were included in the study. Group A was given 6mg of dexamethasone, while group B was given methylprednisolone 40mg twice daily for 10 days. All the collected data was analyzed using SPSS 26.0, and Chi-square was used to find the mortality association between the two groups. A p-value of less than 0.05 was considered significant. The results showed that the age and gender distribution for the methylprednisolone and dexamethasone groups were 56.89±13.3 (M=36, F=38) and 57.69±12.6 (M=38, F=36), respectively. In terms of mortality, 45 patients died in the methylprednisolone group, while 54 people died in the dexamethasone group. There was statistical significance regarding mortality in both groups (p=0.003). In conclusion, the study found that administering 40mg of methylprednisolone twice daily produced better outcomes than 6mg of dexamethasone once daily in treating severe COVID-19 patients in the hospital.